Madrasah as Habitus for Increasing Tolerance in Multi-Religious Society - Salim, Ahmad; Mukhibat, Mukhibat; Hayani, Aida; Wafa’, Muhammad; Assalihee, Muhammadafeefee (IAIN Ponorogo, 2023)
Tolerance is essential in harmonizing people's lives, especially in a multi-religious society. As a legal institution, madrasah is essential in instilling a tolerant attitude that students can apply later in their lives. This study explains the essential role of madrasah as a habitus field for inculcating a tolerant attitude to students using the Bourdieu habitus concept. It employed descriptive qualitative research. The data were collected through observation and in-depth interviews at MTsN 4 Kulon Progo, Yogyakarta. The results show that the madrasah can instill a tolerant attitude in students with the support of teachers as actors. It is a field and social capital (trust, values, and networks) that are integrated in the process of social reproduction of tolerant attitudes to students. The result also provides evidence that the madrasah is not merely an Islamic educational institution that teaches religion from a textual aspect but also a place where universal religious behavior is shaped in society, including an attitude of tolerance. Society will have tremendous confidence in the madrasah when it can contribute significantly to solving various social problems.